2021
DOI: 10.3389/fenvs.2021.653568
|View full text |Cite
|
Sign up to set email alerts
|

The Beach Aquifer Microbiome: Research Gaps and Data Needs

Abstract: Beach aquifers, located in the subsurface of sandy beaches, are unique ecosystems with steep chemical and physical gradients resulting from the mixing of terrestrial fresh groundwater and saline groundwater from the sea. While work has rapidly progressed to understand the physics and chemistry in this environment, much less is known about the microorganisms present despite the fact that they are responsible for vital biogeochemical processes. This paper presents a review of the current state of knowledge of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 89 publications
2
14
0
Order By: Relevance
“…and Bacteroidota were among the dominant phyla, in agreement with most available studies on subterranean estuaries (Archana et al, 2021;Ruiz-González et al, 2021). However, Patescibacteria was the second most dominant phylum reaching up to 23% of local sequences.…”
Section: High Spatial Heterogeneity Of Dominant Microbial Groups Alon...supporting
confidence: 89%
See 2 more Smart Citations
“…and Bacteroidota were among the dominant phyla, in agreement with most available studies on subterranean estuaries (Archana et al, 2021;Ruiz-González et al, 2021). However, Patescibacteria was the second most dominant phylum reaching up to 23% of local sequences.…”
Section: High Spatial Heterogeneity Of Dominant Microbial Groups Alon...supporting
confidence: 89%
“…All this suggests that the spatial distribution of prokaryotic groups observed here will vary seasonally following the temporal variations in aquifer physicochemistry, but whether such seasonal changes will be due to a spatial redistribution of the same microbial taxa or to the growth of new groups peaking at different moments of the year remains unknown. Moreover, there are multiple evidences that a large of the groundwater microbial biomass and activity is concentrated on aquifer surfaces, and that these communities differ taxonomically and functionally from free-living cells (Archana et al, 2021;Ruiz-González et al, 2021), so it is likely that our data, based only in groundwater samples, are providing an incomplete view of the microbial complexity hidden within the Argentona aquifer.…”
Section: Salinity As a Key Driver Of Aquifer Prokaryotic Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This provided us with a valuable opportunity to study the spatial variation of the microbial community structure for different degrees of seawater intrusion. Previous research has shown that groundwater is often rich in inorganic nutrients, including nitrate, phosphate and silicate, while seawater provides more abundant oxygen, salt, sulfate and organic matter ( Archana et al, 2021 ). Therefore, with the different degrees of seawater intrusion, an environmental gradient was formed among G1, G2 and G3, and the corresponding microbial community structure also showed obvious spatial differences.…”
Section: Discussionmentioning
confidence: 99%
“…FSGD sites on the seafloor can be identified through identification of morphologic depressions (pockmarks, sinkholes) through high frequency acoustic seafloor bathymetry mapping and identification of anomalous seafloor fauna and flora associated with a change in water salinity and nutrients input (e.g. Lecher and Mackey, 2018;Archana et al, 2021). Other approaches used to search FSGD sites on a regional scale include mapping radiogenic isotopes that are associated with groundwater (Burnett, 2006;Paldor et al, 2020), shallow physical imaging of resistivity anomalies, survey of small-scale magnetic susceptibility anomalies caused by preservation or diagenetic alteration of iron oxides in sediments (Müller et al, 2011), satellite infrared imagery using e.g.…”
Section: Groundwater Flowmentioning
confidence: 99%